Androgen Receptors Expression in Pituitary of Male Viscacha in relation to Growth and Reproductive Cycle - Verónica Palmira Filippa; Gabriela Judith Rosales; Albana Andrea Marina Cruceño; Fabian Heber Mohamed (International Journal of Endocrinology)
The aim of this work was to study the androgen receptors (AR) expression in pituitary pars distalis (PD) of male viscachas in relation to growth and reproductive cycle. AR were detected by immunocytochemistry and quantified by image analysis. Pituitary glands from fetus, immature, prepubertal, and adult viscachas during their reproductive cycle were used. In the fetal PD, the immunoreactivity (ir) was mainly cytoplasmic. In immature and prepubertal animals, AR-ir was cytoplasmic (ARc-ir) and nuclear (ARn-ir) in medial region. In adult animals, ARn-ir cells were numerous at caudal end. AR regionalization varied between the PD zones in relation to growth. In immature animals, the ARn-ir increased whereas the cytoplasmic expression decreased in relation to the fetal glands. The percentage of ARc-ir cells increased in prepubertal animals whereas the nuclear AR expression was predominant in adult viscachas. The AR expression changed in adults, showing minimum percentage in the gonadal regression period. The variation of nuclear AR expression was directly related with testosterone concentration. These results demonstrated variations in the immunostaining pattern, regionalization, and number of AR-ir cells throughout development, growth, and reproductive cycle, suggesting the involvement of AR in the regulation of the pituitary activity of male viscacha.